Website-Based Point of Sales (POS) Application Design Using The Laravel Framework - Edwin Aji Sentosa; Tutik Khotimah; Rizkysari Mei Maharani (International Journal of Science and Environment (IJSE), 2025)
The data processing process at Toko Karunia in Trangkil Village still relies on manual recording. This method still poses many risks such as inaccurate product recording, slow sales reports, and a higher risk of data loss, all of which have an impact on the work efficiency of the shop owner. The purpose of this research is to solve the problem by designing a web-based Point of Sale (POS) application according to the needs of the store. The application design method uses the waterfall method with the System Development Life Cycle (SDLC) approach. The application design process in this study is carried out sequentially. Starting with requirements analysis, system design, system development, system testing, and system implementation. At the application development stage, the programming language used is PHP with the Laravel framework, with the MySql database. After the application has been designed, it will be tested through the Black Box Testing method. As a result, the main features such as login, managing categories, products, members, suppliers, transaction features, and printing reports function properly. Overall, this POS application improves all aspects such as speed, accuracy, security, and ease of accessing data. This application also strengthens Toko Karunia's position to keep competing in the digital era. Keywords: Point of sale, PHP, Waterfall, Laravel, MySql